Curcumin to inhibit binding of spike glycoprotein to ACE2 receptors: computational modelling, simulations, and ADMET studies to explore curcuminoids against novel SARS-CoV-2 targets. Issue 52 (25th August 2020) - Shanmugarajan, Dhivya; P., Prabitha; Kumar, B. R. Prashantha; Suresh, B.
Abstract : The significant role of curcumin against SARS-CoV-2 drug targets to thwart virus replication and binding into the host system using the computational biology paradigm approach. Abstract : The recent emergence of the novel coronavirus (SARS-CoV-2) has raised global concern as it is declared a pandemic by the WHO. However, to date, there is no current regimen to mitigate the molecular pathogenesis of SARS-CoV-2 virus. Curcuminoids, bioactive ingredients present in Curcuma longa (turmeric), are known to exhibit diverse pharmacological properties. To the best of our understanding to date, SARS-CoV-2 uses angiotensin-converting enzyme 2 (ACE2) for the host cellular entry. This is mediated via proteins of SARS-CoV-2, especially the spike glycoprotein receptor binding domain. Accordingly, our primary objective is to thwart virus replication and binding to the host system, leading us to probe curcuminoids efficiency towards key surface drug target proteins using the computational biology paradigm approach. Specifically, fourteen natural curcuminoids were studied for their possibility of inhibiting SARS-CoV-2. We studied their in silico properties towards SARS-CoV-2 target proteins by homology modelling, ADME, drug-likeness, toxicity predictions, docking molecular dynamics simulations and MM-PBSA free energy estimation. Among the curcuminoids docked to the receptor binding domain of SARS-CoV-2 spike glycoprotein, the keto and enol forms of curcumin form strong hydrogen bond interactions with ACE2 binding residues Q493, T501, Y505, Y489 and Q498. Molecular dynamics simulations, free energy binding and interaction energy validated the interaction and stability of the docked keto and enol forms of curcumin.